2008
DOI: 10.1053/j.gastro.2008.02.084
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic KRAS Induces Progenitor Cell Expansion and Malignant Transformation in Zebrafish Exocrine Pancreas

Abstract: Background and Aims-Although the cell of origin for pancreatic cancer remains unknown, prior studies have suggested that pancreatic neoplasia may be initiated in progenitor-like cells. In order to examine the effects of oncogene activation within the pancreatic progenitor pool, we devised a system for real-time visualization of both normal and oncogenic KRAS-expressing pancreatic progenitor cells in living zebrafish embryos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
124
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(128 citation statements)
references
References 29 publications
4
124
0
Order By: Relevance
“…Homologous recombination leads to accurate replacement of the Ptf1a coding sequences with the eGFP and eGFP-Kras transgene (Davison, Woo Park et al 2008). Their results demonstrate that oncogenic Kras-expressed pancreatic progenitor cells fail to undergo characteristic exocrine differentiation although their initial specification and migration are observed to be normal (Davison, Woo Park et al 2008;Park, Davison et al 2008). Blocks of differentiation leads to abnormal accumulation of the undifferentiated progenitor cells, correlates with the formation of invasive pancreatic cancer.…”
Section: Studies Of Kras-mediated Pancreatic Tumorigenesis With Bacsmentioning
confidence: 99%
See 1 more Smart Citation
“…Homologous recombination leads to accurate replacement of the Ptf1a coding sequences with the eGFP and eGFP-Kras transgene (Davison, Woo Park et al 2008). Their results demonstrate that oncogenic Kras-expressed pancreatic progenitor cells fail to undergo characteristic exocrine differentiation although their initial specification and migration are observed to be normal (Davison, Woo Park et al 2008;Park, Davison et al 2008). Blocks of differentiation leads to abnormal accumulation of the undifferentiated progenitor cells, correlates with the formation of invasive pancreatic cancer.…”
Section: Studies Of Kras-mediated Pancreatic Tumorigenesis With Bacsmentioning
confidence: 99%
“…The studies have also shown that mammalian and zebrafish pancreas are significantly similar in anatomy and histology (Wallace and Pack 2003;Chen, Li et al 2007). Therefore, the Zebrafish has emerged as an experimental model for study of human pancreatic cancer biology (Davison, Woo Park et al 2008;Park, Davison et al 2008). Another benefits of working with zebrafish model is their translucency, which greatly improves the visualization of fluorescent trangenes in both embryos and adult zebrafish (Davison, Woo Park et al 2008).…”
Section: Studies Of Kras-mediated Pancreatic Tumorigenesis With Bacsmentioning
confidence: 99%
“…Using a transgenic reporter line of zebrafish that express GFP under the control of the ela3I (elastase A) promoter, research from the Lin lab has studied the effects of retinoids on exocrine pancreas development . Using pancreasspecific promoters it has been possible to create models of both exocrine and endocrine pancreatic tumors (Yang et al 2004, Park et al 2008. It is possible to envision chemical screens using zebrafish embryos to identify compounds capable of promoting b-cell differentiation, or compounds blocking early stages of transformation in tumor models.…”
Section: Pancreasmentioning
confidence: 99%
“…www.endocrinology-journals.org development (Park et al 2008). By directly observing pancreatic progenitor cells during development, they were able to demonstrate that KRAS G12V expression induces a block in differentiation of exocrine progenitors.…”
Section: Pancreatic Cancermentioning
confidence: 99%
“…Recent comparative genomics analysis of the zebrafish reference genome (Zv9) revealed 26,206 protein-coding genes, with 71% having human orthologues, of which 82% are correlated with diseaseassociated genes in the Online Mendelian Inheritance in Man (OMIM) database 13,14 . Consequently, the zebrafish has been used to model diverse types of human cancers, including neuroblastoma 8 , T-cell acute lymphoblastic leukemia (T-ALL) 15,16 , melanoma 17,18 , Ewing's sarcoma 19 , rhabdomyosarcoma 20,21 , pancreatic carcinoma 22 , hepatocellular carcinoma 23 and myeloid malignancies 24,25 , and has been selected as a cancer model for xenotransplantation studies . To develop such a model ( Figure 1A), one injects a DNA construct containing the gene of interest driven by a tissue-specific promoter into one-cell wild-type embryos.…”
Section: Introductionmentioning
confidence: 99%